The true costs of REACH. A study performed for the Nordic Council of Ministers - Ackerman, Frank; Massey, Rachel (Copenhagen, 2004)
"REACH, the European Union's proposed chemicals policy, is the subject of ongoing controversy -- focusing in particular on its potential costs. This study provides a bottom- up recalculation of the expected costs of the current (October 2003) version of REACH, estimating an 11-year total direct cost of €3.5 billion. A proposed variant, “REACH Plus,” would restore some features of a previous version of REACH, while increasing the total direct cost only to €4.0 billion. The annual cost is around 0.06% of the chemical industry's sales revenue. Two standard economic models imply that total (direct plus indirect) costs should be no more than 1.5 – 2.3 times the direct costs. Economic analysis confirms that costs of this magnitude are unlikely to harm European industry, while several studies have suggested that the health and environmental benefits of REACH will be substantial." (Authors' abstract)